Pembuatan Dan Pengelolaan Website Desa Sebagai Media Informasi di Era Digital di Desa Tejo - Achmad Rizal; Muhamad Khoirur Roziqin; Wafiq Abdul Jalil; Thalisa Septia Firdaus; Milatul Laila Mufidah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
The lack of understanding of Tejo village apparatus, Mojoagung sub-district, and Jombang Regency in making and using village websites due to lack of support from human resources and existing infrastructure has an impact on the lack of awareness of village officials on the importance of using village websites as a means of village information. Only now, village apparatus knowledge regarding the creation and use of websites is still very lacking, so the dissemination of village information through websites has not been done. In this community service activity, a research team from Universitas KH. A Wahab Hasbulloh helped create a village website in Tejo village. In addition, the research team also held training for Tejo village officials to manage the website that had been made. With the creation and training on using websites in Tejo village, it is hoped that village programs and information about Tejo village can be accessed and socialised correctly. The method used in this activity is training in creating and operating village websites. The result of the training on the creation and operation of the Tejo village website is the creation of a village website and the skills of village officials in managing the village website properly and correctly.